1993
DOI: 10.3109/00365599309181257
|View full text |Cite
|
Sign up to set email alerts
|

Urethral Stricture Repair: Results in 179 Patients

Abstract: From 1977 till April 1990 169 operative reconstructions of urethral strictures were carried out in this clinic. 49 patients with a short stricture (less than 2 cm) underwent excision and end to end anastomosis. In 18 patients with a long stricture (2-6 cm) one stage urethroplasty with a transverse distal penile or preputial island of skin flap was used. 102 patients with extensive or otherwise problematic strictures were subjected to two-stage mesh skin graft urethroplasty. In 10 patients with a short strictur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 14 publications
0
5
0
2
Order By: Relevance
“…It is believed, however, that inflammatory strictures are more extensive, generally involving more of the urethra and corpus spongiosum, and are less likely to yield a successful result [17]. Lindell et al [18] reported the highest failure rate in patients with strictures, which was related to prolonged indwelling catheter drainage. In our series, the stricture etiology of the four failure cases was iatrogenic in three patients and infection in one patient.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed, however, that inflammatory strictures are more extensive, generally involving more of the urethra and corpus spongiosum, and are less likely to yield a successful result [17]. Lindell et al [18] reported the highest failure rate in patients with strictures, which was related to prolonged indwelling catheter drainage. In our series, the stricture etiology of the four failure cases was iatrogenic in three patients and infection in one patient.…”
Section: Discussionmentioning
confidence: 99%
“…Numerosas series de UP han documentado excelentes resultados alejados, con una probabilidad de éxito que va desde el 70 al 95%, según el tipo de reconstrucción y el tiempo de seguimiento. En la tabla 1 se muestran los resultados de 10 series de anastomosis término-terminal en la uretra anterior con seguimiento de 4 a 5 años y un éxito promedio superior al 90% [12][13][14][15][16][17][18][19][20][21] . A pesar de que otras técnicas que requieren sustitución uretral con injertos y colgajos no tienen tan buenos resultados, su éxito al menos duplica el de la UIE.…”
Section: Time (Years)unclassified
“…Por su parte, la UP es una alternativa mucho más compleja, de mayor coste, que incluye una gran variedad de técnicas quirúrgicas que requieren experiencia y entrenamiento, y que tienen también mayor morbilidad. Sin embargo, tiene un alto índice de curación definitiva, que puede superar el 90% en casos seleccionados y en manos entrenadas [12][13][14][15][16][17][18][19][20][21][22][23] . En muchos países la UIE ha sido el tratamiento de primera línea, de tal manera que la inmensa mayoría de los pacientes sometidos a UP tienen múltiples UIE previas, y en realidad sólo se piensa en una UP como una alternativa de rescate cuando ya han fracasado una o varias UIE.…”
Section: Discusión Orientada a La Recomendaciónunclassified
“…Various surgical procedures have been developed in the last decades but today the one-stage repair using foreskin or penile skin as onlay urethroplasty seems to yield the best long-term results [12,13,[15][16][17]. Tube urethroplasties suffer from a high stricture rate at the anastomotic sites [13] and a two-stage repair did not show better results compared to one-stage [12,19]. The reported overall success rate with open urethroplasties ranges from 60% to 93%.…”
Section: Urethroplastymentioning
confidence: 99%
“…This is mainly due to patient selection and different types of strictures. In general, short strictures (below 2 cm) apart from those of the membranous Urethra, may best be treated with internal urethrotomy and in case of recurrence with end-to-end anastomosis [1,2,12]. In men without circumcision with longer bulbar and penile urethral strictures the Quartey modification of the Orandi one-stage preputial/penile skin onlay urethroplasty [15] or the transverse preputial island flap technique similar to the technique described by Duckett [5] yields good long-term results.…”
Section: Urethroplastymentioning
confidence: 99%